Implementasi Framework Laravel dalam Perancangan Website Lkd BUMDESMA Kompak Sejahtera menggunakan Metode Prototype - Fatich, El Vionna Laellyn Nurul; Pambudi, Arif Prio; Tafrikhatin, Asni; Yuliyanto, Wakhid (Politeknik Piksi Ganesha Indonesia, 2024)
BUMDESMA as a village-owned business entity needs a website for a wider information dissemination process. Not only as a means of sharing information quickly, accurately and easily, websites are also used to maintain the credibility and existence of a company in developing its business. BUMDESMA Kompak Sejahtera Lkd is one of the BUMDESMA that does not yet have a website for disseminating information or means for conducting business transactions. So far, information dissemination has only been limited to distributing printed brochures offline. To increase the dissemination of information on the existence and existence of BUMDESMA Kompak Sejahtera Lkd, in this research a BUMDESMA website was designed using the prototype method. To get an effective and efficient website design, the Laravel framework was chosen as the solution. After designing the BUMDESMA website, it is hoped that information about BUMDESMA Kompak Sejahtera Lkd will become wider so that it can help increase business activities at BUMDESMA.